Barriers to Consuming Dietary Protein and Cardiometabolic Risk Factors Among Low-Income and Homeless Adults (P04-089-19). (13th June 2019) - Walker, Sam; Fitzpatrick, Kevin; Baum, Jamie
Abstract: Objectives: Over 40 million Americans identify as food insecure and lack access to adequate food. The objective of this study was to identify the barriers to consuming dietary protein and to determine how lack of access to dietary protein is associated with cardiometabolic risk factors in food insecure (FI) and homeless adults Methods: Participants were recruited during intake at a medical outreach event for homeless and low-income adults living in Northwest Arkansas. A total of 96 adults (62 male and 33 female; 50.3 ±13.3 y) completed the survey. Subjects were asked to verbally respond to questions regarding their current housing and food security status, dietary habits, and general access to medical care. Cardiometabolic risk factors (BMI, glucose, and blood pressure) were also measured. Data was analyzed using Statistical Package for the Social Science v25. Results: A total of 74.8% of participants reported some degree of FI. The majority of FI participants reported high- (32.6%) followed by moderate- (31.5%) and low-severity (16.3%); almost half of the participants (44.8%) reported being homeless. Barriers to protein consumption were positively correlated with FI (r = .36; P < .001). Over 70% of participants reported at least one barrier that prevented them from consuming protein. The majority reported that cost was the most important barrier to accessing protein (58%), followed by convenience (25%) and time available to prepare it (22%). In part, due to these and other barriers, more than one-third of respondents reported consuming protein fewer than 5 times per week. There were no associations between FI and cardiometabolic risk factors. Nevertheless, the majority of participants screened (88%) had blood pressure above 120/80 mm and had elevated blood glucose (39.7%) and 76% were either overweight or obese. Conclusions: Barriers to consuming dietary protein exist among homeless and low-income adults. Cost and convenience are the two most important barriers among this population subgroup; persons reporting barriers to protein access also reported higher levels of FI. Additionally, food insecurity and homelessness may increase risk for irregular cardiometabolic biomarkers. Future research will focus on how to overcome these barriers and improve markers of cardio metabolic health in adults experiencing FI. Funding Sources: American Egg Board/Egg Nutrition Center.